2017
DOI: 10.1037/tra0000147
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of posttraumatic stress symptoms after civilian or deployment traumatic event experiences.

Abstract: Objective Growth mixture model studies have observed substantial differences in the longitudinal patterns of posttraumatic stress symptom (PTSS) trajectories. This variability could represent chance iterations of some prototypical trajectories or measurable variability induced by some aspect of the source population or traumatic event experience. Testing the latter, we analyzed a nationally representative sample of U.S. Reserve and National Guard members to identify the influence of civilian versus deployment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…When we evaluated risk factors for initial PTSD reactions, the risk factors we identified (i.e. female gender, non-white race, prior interpersonal trauma, and assault) were consistent with prior research (Bryant et al, 2015; Fink et al, 2017; Sripada et al, 2017). These findings suggest that these risk factors should be included in prediction tools to identify survivors at risk for initially high levels of PTSD symptoms as part of routine post-injury psychiatric evaluations.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…When we evaluated risk factors for initial PTSD reactions, the risk factors we identified (i.e. female gender, non-white race, prior interpersonal trauma, and assault) were consistent with prior research (Bryant et al, 2015; Fink et al, 2017; Sripada et al, 2017). These findings suggest that these risk factors should be included in prediction tools to identify survivors at risk for initially high levels of PTSD symptoms as part of routine post-injury psychiatric evaluations.…”
Section: Discussionsupporting
confidence: 76%
“…One important characteristic appears to be the type of PTE to which participants were exposed, such that a consistently low trajectory is more common following less severe PTEs (e.g. Fink et al, 2017). A second source of heterogeneity could be timing of assessment, with the length of follow-up across trajectory studies ranging from months to several years post-trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal and trajectory-based examinations of resilience (e.g. Andersen, Karstoft, Bertelsen, & Madsen, 2014; Fink et al, 2017; Norris, Tracy, & Galea, 2009) that measure the timing of traumatic events and dates of onset for diagnostic conditions are essential. The examination of new-onset or ongoing stressors in these studies is suggested to provide a more nuanced picture of the process of resilience in the face of ongoing adversity to better understand the relationships among resilience antecedents, attributes, consequences, and long-term trajectories of resilience and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the course of PTSD may hold some answers to the trajectory of adjustment disorder over time. There have been a number of studies that have examined the trajectory of PTSD symptoms over time [29,30,31,32,33,34,35]. Generally, these studies show that the majority of those who are exposed to trauma typically fall into one of four to five prototypical trajectories (see Figure 1).…”
Section: Course and Trajectorymentioning
confidence: 99%